Challenges in diagnosing traumatic ulcers: case report: Tantangan dalam menegakkan diagnosis ulser traumatik: laporan Kasus - Devi Nasution; Riani Setiadhi (Makassar Dental Journal PDGI Makassar, 2019)
Background: Traumatic ulcer is a common ulcer lesion that similar to other oral lesions such as oral squamous cell carcinoma (OSCC) making it a challenge for clinicians in establishing the diagnosis. Objective: Describing the challenges and difficulties in establishing the diagnosis of a confusing oral lesion. Case report: A 48-year- old woman complained of a painful indurated lesion on her left lateral tongue for 3 weeks, accompanied by numbness causing difficulties in eating. There were sharp 37 and 38 teeth. The ulcer’s clinical feature was similar to OSCC makingitdifficulttoestablishthediagnosis.Basedontheseclinicalfindings, the patient was diagnosed as traumatic ulcer and differentiated diagnosis with OSCC. The patient was treated with topical corticosteroid, vitamin B12, folic acid and extraction of the sharp teeth. Conclusions: A thorough anamnesis and recognizing clinical findings are the keys to establish diagnosis appropriately in order to provide proper treatment.